New Advances on Nutrients Recovery from Agro-Industrial and Livestock Wastes for Sustainable Farming - Cucina, Mirko; Regni, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book collects six papers published in the Agronomy Special Issue "New Advances on Nutrients Recovery from Agro-Industrial and Livestock Wastes for Sustainable Farming" that aim to furnish new information on nutrients recovery from organic wastes.